Health promotion, disease prevention and public health - Nowicka, Grażyna (Studia Ecologiae et Bioethicae, 2003)
The maintenance of good health throughout the entire life course is of great importance for individuals and also for the whole population and strongly influences economic and cultural development. Therefore, health promotion, prevention of health abnormalities, and diseases recognized as leading causes of premature deaths have been accepted as very important activities in the area of public health. In this article, the major factors influencing public health and basic tasks for public health improvement are presented.